Tindak Tutur Ekspresif dalam Podcast Close The Door Deddy Corbuzier Pada Episode â€œCoba Ibu Jawab JHT Gimanaâ€ - Milli Ana (ESTETIK : Jurnal Bahasa Indonesia, 2022)
In an interaction, speakers and speech partners need good communication to express information that fits the context. Expressive speech acts are the way speakers express their intentions, thoughts, and feelings. The purpose of this study is to describe the function, and meaning of expressive speech acts contained in the Deddy Corbuzier podcast episode "Coba Ibu Bawah Coba JHT". The method used in this research is descriptive qualitative combined with pragmatic studies. Data collection is done by recording, listening, and taking notes. While the data analysis used in the research is; transcription, identification, analysis, review and conclusion. The findings or results of this study explain the implied context/implications conveyed by speakers and speech partners to all people who watch this podcast about the Job Creation Law that is being discussed.